2010
DOI: 10.1038/onc.2010.448
|View full text |Cite
|
Sign up to set email alerts
|

Reversion-inducing cysteine-rich protein with Kazal motifs interferes with epidermal growth factor receptor signaling

Abstract: The reversion-inducing cysteine-rich protein with Kazal motifs (RECK) gene had been isolated as an antagonist to RAS signaling; however, the mechanism of its action is not clear. In this study, the effect of loss of RECK function was assessed in various ways and cell systems. Successive cell cultivation of mouse embryonic fibroblasts (MEFs) according to 3T3 protocol revealed that the germline knockout of RECK confers accelerated cell proliferation and early escape from cellular senescence associated with downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 56 publications
1
22
0
2
Order By: Relevance
“…38 Since RECK has been shown to bind the ligand binding IL-6R and gp130, the signal transducing subunit of the IL-6 receptor heterodimer, 39 it may interfere with IL-6 signaling by blocking IL-6 interaction with the IL-6R/gp130 heterodimer. RECK also blocks Epidermal Growth Factor Receptor transactivation, 40 which is known to contribute to CF proliferation. 41 Thus, it is possible that HDAC inhibitors can blunt cardiac fibrosis and adverse remodeling through two different mechanisms: that is, by directly targeting MMP9 and IL-18 induction, and indirectly by restoring RECK expression.…”
Section: Discussionmentioning
confidence: 99%
“…38 Since RECK has been shown to bind the ligand binding IL-6R and gp130, the signal transducing subunit of the IL-6 receptor heterodimer, 39 it may interfere with IL-6 signaling by blocking IL-6 interaction with the IL-6R/gp130 heterodimer. RECK also blocks Epidermal Growth Factor Receptor transactivation, 40 which is known to contribute to CF proliferation. 41 Thus, it is possible that HDAC inhibitors can blunt cardiac fibrosis and adverse remodeling through two different mechanisms: that is, by directly targeting MMP9 and IL-18 induction, and indirectly by restoring RECK expression.…”
Section: Discussionmentioning
confidence: 99%
“…It also seems to be possible that RECK also regulates other signaling molecules and pathways included in angiogenesis [38]. Kitajima et al [39] identified epidermal growth factor receptor/rat sarcoma signaling as one of those pathways that are influenced by RECK. Takeuchi et al [29] have shown an inverse correlation between the RECK level and the level of vascular endothelial growth factor expression and suggested suppression of angiogenesis by limiting vascular endothelial growth factor availability.…”
Section: Discussionmentioning
confidence: 99%
“…MEFs were isolated from littermate wild type, Rb −/− embryos and Srebf1 −/− embryos as described previously, 57 and maintained in α modified Eagle’s medium (MEMα, #135-15175, Wako, Osaka, Japan) supplemented with 10% fetal bovine serum and 1% phosphatidylserine.…”
Section: Methodsmentioning
confidence: 99%